Substantiation of Enterprise Market Cost in Conditions of Economy Transformation - V. I. Pohabov; V. A. Ustinovich (Наука и техника)
The paper shows actuality and problems concerning estimation of company’s value in conditions of economy transformation in the Republic of Belarus. It is proposed to apply a complex method for estimation of industrial enterprise value. The paper considers the influence of economic development phase and estimation purpose on its cost.